Designing of Monitoring System for Electricity Power Consumption using Microcontroller and IoT - Rozak, Mohamad; Setyadi, Denys T; Farisy A, M Fayadh Z; Abdillah, Fadhli; Rijayana, Iwan (International Journal of Psychosocial Rehabilitation, 2020)
Modernization has indeed had a huge impact on the lives of today’s societies, and the modern age has all sorts of technological implications. Household and electricity tools have followed closely, as is evident by the development in prepaid and digitized meter. However, in doing so, society will not be able to control and monitor this specific use of power. In the above view of the problem, the author came up with the idea of creating a prototype electrical power monitoring device that could operate automatically. They use microcontroller arduino uno with ACS712 current sensors, and air-conditioned module sensors 1 phase (ZMPT101B) along with LCD. The way this works is to detect electrical currents entering the load of electrical equipment on ACS712 sensors, and the voltage coming in on sensors (ZMPT101B), the sensor system receives current and the voltage at the entrance as it directs the microcontroller module arduino uno to be systematicaly combined with a power equation (Wh) Wh = Ixt (stream x time) So we get the electrical power that’s used during use. And for record-keeping. We added some tweaked hardware IOT Which is the ESP8266 wireless module as a data bridge from device to cloud using Internet media.